Determinants of Credit in Indonesia's Agricultural Sub-Sector: Panel Data Analysis - Dini Yuniarti; Arif Sapto Yuniarto (Universitas Ahmad Dahlan, 2021)
Credit has a role in agricultural development and the income of small farmers which will reduce poverty levels. However, the portion of credit in the agricultural sector is still relatively small. This study aims to examineÂ determinants of credit in the agricultural sub-sector. The factors include credit rating, credit interest rates, Gross Domestic Product and the number of farmers in the agricultural sub-sector. The data used are secondary data, a combination of cross-sectional data including the agricultural sub-sector, namely food crops, horticultural crops, plantations and livestock and seres times including 2011-2019. The analysis tool used is the regression data panel. The study results show that the number of creditors in the agricultural sector is positive and significant by the number of farmers and Gross Domestic Product, while interest does not affect the credit rating of the agricultural sub-sector. Policies that can be taken are to increase the Gross Domestic Product of the agricultural sector to increase the capacity of farmers. In addition, to increase farmers' access to financial institutions, financial education is needed, so that it will increase financial literacy.